Bridging Nigeria energy gap by utilizing her coal (2017)
Many nations who meet their energy generation requirements are one way or the other tapping from the vast resources which is inherent in coal. A wide gap exists between the energy requirement of the Nigerian populace and the generated amount. This can be bridged by the utilization of its vast amount of bituminous coal in her reserves, with favourable properties of low percentage moisture and ash which is an advantage in terms of handling costs, ease of transportation and better overall system efficiency. The percentage moisture value for the analyzed sample was 5.0 percent while the percentage ash value was 6.6 percent. Both determined values are relatively low when compared to results of the analysis reported for some other countries coal.